2020
DOI: 10.1177/2399808320974693
|View full text |Cite
|
Sign up to set email alerts
|

Using data mining to explore the spatial and temporal dynamics of perceptions of metro services in China: The case of Shenzhen

Abstract: Improving perceptions of service quality is a promising planning strategy for increasing the attractiveness and retaining the ridership of public transport systems. The widespread use of social media presents an opportunity to investigate the performance of transport services from the customer’s perspective. This study proposes a framework for integrating quantitative and qualitative analyses to investigate the perceptions of transport services by mining data from social media. We utilise Sina Weibo data relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 42 publications
0
8
1
Order By: Relevance
“…Both geo-tagged social media data and GPS location data have been widely used for detecting latent patterns in cities. Social media data has been widely used to describe activities associated with specific places such as parks, restaurants, coffee places, and transit stations [ 21 , 24 , 25 , 27 29 ]. In comparison, GPS data provides more flexibility to be aggregated at different spatial unit across spatial scales [ 19 ].…”
Section: Data Descriptionmentioning
confidence: 99%
“…Both geo-tagged social media data and GPS location data have been widely used for detecting latent patterns in cities. Social media data has been widely used to describe activities associated with specific places such as parks, restaurants, coffee places, and transit stations [ 21 , 24 , 25 , 27 29 ]. In comparison, GPS data provides more flexibility to be aggregated at different spatial unit across spatial scales [ 19 ].…”
Section: Data Descriptionmentioning
confidence: 99%
“…Urban computing brings powerful interdisciplinary computational techniques to the study and application in urban areas (Zheng et al, 2014). Luo and He (2021) utilised VGI data (Sina Weibo data) and applied urban computing (text mining) to propose a framework to investigate the perceptions of transport services. This research identified key service areas for immediate improvement of metro systems more effectively over the long term.…”
Section: Urban Computing and Smart City Applicationsmentioning
confidence: 99%
“…In the realm of public transportation, service quality, and government intervention are pivotal in shaping the effectiveness and efficiency of transportation systems (Luo & He, 2021;Morton et al, 2016;Obsie et al, 2020). Research has shown that improving perceptions of service quality is essential for increasing the attractiveness and retaining the ridership of public transport systems (Luo & He, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In the realm of public transportation, service quality, and government intervention are pivotal in shaping the effectiveness and efficiency of transportation systems (Luo & He, 2021;Morton et al, 2016;Obsie et al, 2020). Research has shown that improving perceptions of service quality is essential for increasing the attractiveness and retaining the ridership of public transport systems (Luo & He, 2021). Understanding the service quality of public transportation based on users' perceptions is vital for local governments and transit service providers in planning efforts to enhance system performance (Obsie et al, 2020).…”
Section: Introductionmentioning
confidence: 99%